Ultrastructure of Spermatogenesis in the Short-Tailed Fruit Bat, Carollia perspicillata ( Chiroptera: Phyllostomidae: Carollinae) - Beguelini, Mateus R. [UNESP]; Bueno, Larissa M. [UNESP]; Caun, Dianelli L. [UNESP]; Taboga, Sebastiao R. [UNESP]; Morielle-Versute, Eliana [UNESP] (Wiley-Blackwell, 2014)
Among species of the Chiroptera, spermatogenesis and the fully differentiated spermatozoa differ in morphological and ultrastructural detail. This study therefore aimed to ultrastructurally characterize the spermatogenesis and the spermatozoa of Carollia perspicillata (Phyllostomidae) and compare the process with other species of bats and mammals. The differentiation of spermatogonia is similar to other bats and to Primates, with three main spermatogonia types: A(d), A(p), and B. Meiotic divisions proceed similarly to those of most mammals and spermiogenesis is clearly divided into 12 steps, in the middle of the range of developmental steps for bats (9-16 steps). The process of acrosome formation is similar to that found in Platyrrhinus lineatus, with the acrosome formed by two different types of proacrosomal vesicles. The ultrastructure of the spermatozoon is similar to other bats already described and resembles the typical mammalian sperm model; however, its morphology differs from other mammals such as marsupials and rodents, on account of a simpler spermatozoon head morphology, which indicates a pattern that is more closely related to the sperm cells of humans and other primates. Our data demonstrated that spermatogenesis in C. perspicillata presents great ultrastructural similarities to P. lineatus. This pattern is not surprising, because both species belong to the same family (Phyllostomidae); however, it is observed that C. perspicillata presents some characteristics that are more closely related to phylogenetically distant species, such as Myotis nigricans (Vespertilionidae), which is a fact that deserves attention. J. Morphol. 275:111-123, 2014. (c) 2013 Wiley Periodicals, Inc.
Keywords: Chiroptera; Carollia perspicillata; Spermatogenesis; Spermiogenesis